Complementary Roles of the Classical and Lectin Complement Pathways in the Defense against Aspergillus fumigatus - Rosbjerg, Anne; Genster, Ninette; Pilely, Katrine; Skjoedt, Mikkel-Ole; Stahl, Gregory L.; Garred, Peter (Frontiers in Immunology, 2016)
Aspergillus fumigatus infections are associated with a high mortality rate for immunocompromised patients. The complement system is considered to be important in protection against this fungus, yet the course of activation is unclear. The aim of this study was to unravel the role of the classical, lectin and alternative pathways under both immunocompetent and immunocompromised conditions to provide a relevant dual-perspective on the response against A. fumigatus. Conidia (spores) from a clinical isolate of A. fumigatus were combined with various human serum types (including serum deficient of various complement components and serum from umbilical cord blood). We also combined this with inhibitors against C1q, mannose-binding lectin (MBL) and ficolin-2 before complement activation products and phagocytosis were detected by flow cytometry. Our results showed that alternative pathway amplified complement on A. fumigatus, but required classical and/or lectin pathway for initiation. In normal human serum this initiation came primarily from the classical pathway. However, with a dysfunctional classical pathway (C1q-deficient serum), lectin pathway activated complement and mediated opsonophagocytosis through MBL. To model the antibody-decline in a compromised immune system, we used serum from normal umbilical cords and found MBL to be the key complement initiator. In another set of experiments serum from patients with different kinds of immunoglobulin insufficiencies showed that the MBL lectin pathway contribution was highest in the samples with the lowest IgG/IgM binding. In conclusion, lectin pathway appears to be the primary route of complement activation in the absence of anti-A. fumigatus antibodies, whereas in a balanced immune state classical pathway is the main activator. This suggests a crucial role for the lectin pathway in innate immune protection against A. fumigatus in immunocompromised patients.